Pertumbuhan Dan Produksi Tanaman Sawi Melalui Aplikasi Pupuk Organik Lumpur Laut Dengan Pupuk Kandang - Jacob Richard Patty; Christoffol Leiwakabessy (JURNAL PERTANIAN KEPULAUAN, 2023)
The growth of mustard plants is influenced by the availability of nutrients through the application of fertilizers. Manure and sea mud are one type of biological fertilizer. The study aims to determine the optimal dose of sea mud and manure for the growth and production of mustard plants. The study design was a randomized group design consisting of 2 factors and repeated 3 times. The first of Sea Mud treatment (L) consists of levels, namely: L0 = Control; L1=500 g, L2= 750 g. L3 1000 g. The second factor is that the dose of manure consists of levels, namely: P0=without manure; P1=120 g, P2=160 g: and P3 = 200g. The results showed that L3 treatment was able to increase plant height, while the number of leaves was best in L2 treatment. This treatment was also able to increase the number of leaves, fresh weight and dry weight but between L2 and L3 treatments did not differ markedly. P3 manure treatment is able to increase the best number of leaves, while fresh weight is best P2 treatment. The interaction between treatments only occurred in plant height and leaf area parameters at 17 HST observations.